If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 6 = 4x + 101 Reorder the terms: 6 + 9x = 4x + 101 Reorder the terms: 6 + 9x = 101 + 4x Solving 6 + 9x = 101 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 9x + -4x = 101 + 4x + -4x Combine like terms: 9x + -4x = 5x 6 + 5x = 101 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + 5x = 101 + 0 6 + 5x = 101 Add '-6' to each side of the equation. 6 + -6 + 5x = 101 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 101 + -6 5x = 101 + -6 Combine like terms: 101 + -6 = 95 5x = 95 Divide each side by '5'. x = 19 Simplifying x = 19
| 8(2K-1)=4k-28 | | -5=-2+l | | 9(2y-8)-(2y+2)= | | f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) |